CHANGES IN THE DEPOSITION OF TERRESTRIAL ORGANIC MATTER ON THE LAPTEV SEA SHELF DURING THE HOLOCENE: EVIDENCE FROM STABLE CARBON ISOTOPES - Mueller-Lupp T.; Bauch H.A.; Kassens H.; Erlenkeuser H.; Hefter J.; Thiede J. (My University, 2000)
Stable carbon isotope ratios in the organic fraction of surface sediments from the Laptev Sea shelf were analyzed in order to study the modern distribution pattern of terrestrial organic matter. The δ13Corg signature of the surface sediments range from -26.6‰ near the coastal margin to -22.8‰ in the north towards the outer shelf. Characterizing the possible sources of organic matter by their δ13Corg signature reveals that the terrestrial influence reaches further north in the eastern than in the western Laptev Sea. Downcore records of the δ13Corg, measured on three AMS 14C-dated cores from water depths between 46 and 77 m, specify the spatial and temporal changes in the deposition of terrestrial organic matter on the Laptev Sea shelf during the past 12.7 ka. The major depositional changes of terrestrial organic matter occurred between 11 and 7 ka and comprised the main phase of the southward retreat of the coastline and of the river depocenters due to the postglacial sea level rise.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен